Intended and enacted curricula: tracing the trajectory of an enduring problem - Sylvan Blignaut (Acta Academica, 2009)
This article reviews the literature on educational change and investigates the complex nature of putting educational ideas into practice. It also sheds light on the similarity between the intended and the implemented curriculum by arguing that a preoccupation with two conventional models of curriculum implementation has foiled meaningful classroom practice. An alternative model that could significantly enhance our understanding of implementation is suggested. Focusing on why and how teachers’ understanding of curriculum policy is critical to the translation of policy into practice, alternative ways in which policy might be conceived, developed and put into practice are considered.